Getting Your Letters Wrong: Early Modern Epistolary Writing. - Bayer, Gerd (SEDERI, Yearbook of the Spanish and Portuguese Society for English Renaissance Studies, 2024)
Letters have played a central role in the development of various forms of literary culture. This article argues that it is through the tropes of miscarriage, deceit, and betrayal that early modern writers and audiences frequently encountered epistolary forms of communication. By looking at various examples from Renaissance and Restoration fiction and literary culture, the article demonstrates that this period was marked by inconsistencies, experimentation, and negotiations. Letters at the time provided writers with an opportunity to showcase the flexibility and malleability of language. The letter, indeed, represented the semantic in-betweenness that links factuality and fiction.
Keywords: Epistolarity; genre; history of the novel; Renaissance fiction; Restoration fiction.